Aplicación de la técnica de Valor Ganado como herramienta de control de avance y costos para los Túneles de Desvío del P.H. Reventazón - Jiménez-Solís, Alberto José (Instituto Tecnológico de Costa Rica, 2010)
The following graduation project involves the Earned Value management (EV) implementation in the diversion tunnels of the Reventazón Hydroelectric Project. Among the project’s main objectives, it has been proposed to study the current methodology for controlling and monitoring the work in the Hydroelectric Projects of the Instituto Costarricense de Electricidad. Additionally, some improvements were made in the template used by the management project department (this template monitors the advances and cost performances). Excel Software and Visual Basic applications were employed to make possible the advancements. Once the model was completed, we proceeded applying it into the current running activities, which are:  Open-pit.  Slope stabilization.  Underground excavation. With the aim of understanding even more the behavior of the activities, we made an analysis using the Earned Value management (EV) in the first biweekly (8-15) implementation. When we got the results, we established the parameters to continue monitoring biweekly the progress. With the performance efficiency results, we create biweekly a new analysis of the study (16-21). It provided future forecast trends about the total cost for each activity, the possible date completion and the recommendations for each court date. Finally, this graduation project gives the department a set of conclusions and suggestions on the conduct of the activities up to the week 21. In addition, it states our personal view of the current situation and the possible action plan.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Recurso hídrico; Control de obras; Proyecto hidroeléctrico; Evalución del desempeño; Gestión de proyectos